MAGNETIC POWER ELECTRIC BOARD SEBAGAI MEDIA AJAR UNTUK MENINGKATKAN KREATIVITAS SISWA PADA PEMBELAJARAN MAGNET - Arghob Khofya Haqiqi; Sutikno Sutikno; Masturi Masturi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
physics learning in senior high school currently should be more emphasis not only on the aspect of knowledge; but also for the skill and creativity of students. The subject matter is one of the magnet material taught in senior high school students. Learning model that uses only teaching media magnet students tend to only recognize the concept of a magnet without knowing the application currently of magnets. If the magnetic poles juxtaposed same poles will repel each other. By utilizing the magnetic properties of this we can create an instructional media to drive a dynamo that can generate electricity. Magnetic electric power board is an instructional media that can be developed as a lesson in the magnet. By using this instructional media students will learn concepts of magnetic as well as learn about the magnet applications for rotating dynamo which could generate electricity source. Learning to use a magnetic board electric power is expected that students will be more clearly in studying the magnetic material and the creativity of students is expected to increase because students directly know the benefits of magnets that can be applied in everyday life as a currently alternative electrical energy source.Keywords: electric board; creativity; magnetic power; instructional media.